The Influence of Equal Employment Opportunities and Islamic Work Values on The Quality of Work LIfe of Employees CV. Profish International - Yunizar Yunizar; Aufa Akmal Habibie (Sekolah Tinggi Ilmu Bahasa Arab Darul Ulum Banyuanyar Pamekasan, 2024)
Nowadays, several companies recognize the value of employee loyalty as one of the tools for their growth. Improving the quality of work life of employees is one approach to maintaining employee loyalty and increasing job satisfaction. The purpose of this study is to find out how the influence of equal employment opportunities and Islamic work values variables on the quality of work life. This research was conducted at CV. Profish Internasional which is a company that has a focus on the world of fisheries from cultivation to the distribution of fresh water fish. The population used in the study were all employees of C.V Profish Internasional, totaling 113 people. By using the Isaac and Michael formula, the sample in this study was 89 people. Data analysis used Patrial Least Square-Structural Equation Model or PLS-SEM analysis using SmartPLS. The results show that equality of employment opportunities and Islamic work values have a significant influence on the quality of work life of CV Profish International employees